Saberes y prácticas sobre el cuidado de niños y niñas con enfermedades crónicas respiratorias en una comunidad indígena en el Cauca - Tunubala Reyes, Jhonny Norberto (Universidad Antonio Nariño, 2023)
The most recent data found is from a 2010 study on mortality in indigenous children carried out by the Pan American Health Organization PAHO in which shows the high mortality rate in indigenous youth who compared to non-indigenous is higher, reaching 60% higher the mortality in indigenous children(1), which reflects the inequity in health of these communities, on the other hand the united nations warn about the high incidence of chronic diseases in communities